MORPHOFUNCTIONAL APPROACH TO THE TECHNICAL AND TACTICAL TRAINING OF YOUNG GRECO-ROMAN WRESTLERS: INTERNATIONAL EXPERIENCE - Madaminov Khayrullo Akhmadjonovich (The Conference Hub, 2025)
This article highlights the significance and effectiveness of a morphofunctional approach in optimizing the technical and tactical training of young Greco-Roman wrestlers. The necessity of developing individualized training programs based on an in-depth study of athletes’ morphological and functional characteristics is substantiated. In particular, international experience from countries such as Germany, Russia, the USA, Japan, and Turkey is analyzed in terms of how morphofunctional indicators are applied in the technical and tactical preparation of young wrestlers. The study emphasizes that muscle strength, speed, endurance, reaction time, and anthropometric parameters are decisive factors in the development of technical and tactical skills. Moreover, it is underlined that innovative technologies, monitoring systems, and scientific-methodological approaches employed in foreign countries have practical significance for improving the preparation of Uzbek athletes. The article reveals the role and prospects of international experience in organizing training tailored to the individual capacities of young athletes.
Keywords: Greco-Roman wrestling, young athletes, technical and tactical training, morphofunctional approach, international experience, individualized training, anthropometric indicators, sports physiology, innovative technologies, monitoring system.